Anti-inflammatory properties of an A3 adenosine receptor agonist, piclidenoson, in a model of human peripheral blood mononuclear cell culture - Kozić, Ljiljana; Mališ, Vanja; Drakul, Marija; Rakočević, Sara; Bokonjić, Dejan; Mihajlović, Dušan (Vojnosanitetski pregled, 2025)
Background/Aim. Piclidenoson (CF101, IB-MECA), a selective agonist of the A3 adenosine receptor (A3AR), is used in clinical trials for the treatment of psoriasis. Emerging data from in vitro and in vivo studies suggest that piclidenoson possesses anti-inflammatory and immunomodulatory properties, but its action on human peripheral blood mononuclear cells (PBMCs) remains unknown. The aim of this study was to examine the anti-inflammatory effects of piclidenoson in a model of phytohaemagglutinin (PHA)-stimulated human PBMCs culture. Methods. Human PBMCs were isolated from the venous blood of healthy donors (n = 4) and treated with different concentrations of piclidenoson. Flow cytometry and the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) test were used to determine cell viability, while the MTT method and the carboxyfluorescein succinimidyl ester (CFSE) staining method were used to analyze the effect of piclidenoson on cell proliferation. Levels of tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-1β, IL-23, IL-36, IL-5, interferon (IFN)‐γ, IL-17, and IL-10 were measured using a specific sandwich enzyme-linked immunosorbent assay (ELISA). Results. The results of cytotoxicity tests showed that the highest applied concentration of piclidenoson (1,500 nM) reduced the metabolic activity of PBMCs (p
Keywords: blood; cytokines; flow cytometry; inflammation; in vitro techniques; leukocytes, mononuclear; phytohemagglutinins; receptors, purinergic